2014
DOI: 10.7243/2050-1218-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Porcine urinary bladder extracellular matrix activates skeletal myogenesis in mouse muscle cryoinjury

Abstract: Background: Accelerated muscle regeneration is highly desirable after direct injury in trauma patients. Though the advantage of extracellular matrix extracted from porcine urine bladder (UBM) on tissue regeneration is feasible, the mechanisms by which skeletal myogenesis is improved are not clear. The current study aim was to determine whether UBM affects skeletal satellite cells during muscle repair after cryoinjury. Methods: RAG2-/-, γc -/-mice underwent bilateral gluteus muscle cryoinjury under general anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The same report showed that placement of extracellular matrix immediately after injury improved muscle function and brotic tissue remodeling, but there was no evidence of myo ber regeneration at day 28 [28]. We previously observed increased myogenesis in a cryoinjured mouse with UBM treatment [29]. In vitro, we found that UBM increases the protein expression of the proliferation marker PCNA in the mouse myoblast C2C12 cells, supporting a direct effect of UBM on muscle cells (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…The same report showed that placement of extracellular matrix immediately after injury improved muscle function and brotic tissue remodeling, but there was no evidence of myo ber regeneration at day 28 [28]. We previously observed increased myogenesis in a cryoinjured mouse with UBM treatment [29]. In vitro, we found that UBM increases the protein expression of the proliferation marker PCNA in the mouse myoblast C2C12 cells, supporting a direct effect of UBM on muscle cells (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…UBM has been shown to promote regeneration in soft tissue injury through a number of mechanisms. Remodeling UBM was shown to shift the local macrophage response in vivo towards a pro-healing, anti-inflammatory phenotype (13), and recruits progenitor cell proliferation and differentiation after traumatic muscle injury in mice (14). UBM similarly promoted muscle repair in patients with volumetric muscle loss in a clinical study (15).…”
Section: Introductionmentioning
confidence: 99%
“…This protein is required for the fusion of myogenic precursor cells to either new or previously existing fibers during the process of differentiation. In our previous study, we showed that MRFs, especially myogenin, increased in newly generated myotubes in mouse muscle following local cryoinjury (24). However, myogenin also contributes in the activation of muscle wasting.…”
Section: Discussionmentioning
confidence: 99%